The Effect Of Business Analytics And Organizational Green Culture On Green Competitive Advantage Moderated By Collaborative Competence - Merna Surjadi; Tandry Whittleliang Hakki; Daniel Chandru Khatwani (Dinasti Publisher, 2024)
The era of globalization and the increasing level of corporate competition have changed the industrial sector business in managing companies both internally and externally. Internal management not only maximizes tangible company resources, but also intangible ones in the process of maximizing the value of its company (Widhiastuti et al., 2018). Resources that are predicted to affect company value are Green Competitive Advantage and integrated reporting. According to Wijayanto et al. (2019) green competitive advantage is a condition of positional advantage where the company has a successful strategy, and is difficult to imitate. Competitive advantage is the company's ability from its resources to achieve performance excellence over its competitors (Roos Ana et al., 2021). This study aims to analyze the influence of Business Analytics and Organizational Green Culture on Green Competitive Advantage and analyze the role of Collaborative Competence as a moderation of the influence of Business Analytics and Organizational Green Culture on Green Competitive Advantage. This study uses a quantitative correlational method where sampling is done using the Slovin formula and using purposive sampling techniques and data collection methods through distributing questionnaires. The study uses SPSS 25.00 and hypothesis testing uses Multiple Regression Analysis. This study uses primary data which is done by distributing questionnaires to students in the cities of Jakarta and Bandung. Based on the results of this study, it shows that Business Analysis and Green Organizational Culture have an effect on Green Competitive Advantage. Collaborative Competence strengthens the influence of Business Analysis on Green Competitive Advantage but Collaborative Competence strengthens the influence of Business Analysis on Green Competitive Advantage